A new connecting technique in partial replantation of a ruptured peritoneal dialysis catheter - Yaeni Kim; Prashant C. Dheerendra; Yong-Soo Kim (The Korean Society of Nephrology, 2014)
Peritoneal dialysis catheter ruptures have been managed by immediate removal and subsequent reinsertion of the catheter which inevitably entails interruption in peritoneal dialysis and a need for vascular access. A 36-year-old man on continuous ambulatory peritoneal dialysis complaining of dialysate leakage was found to have a small rupture near the outer cuff of the peritoneal dialysis catheter. Rather than employing the traditional method of exchanging the whole catheter, a partial replantation procedure to salvage the still-functioning conduit was performed. Two peritoneal dialysis adaptors were used to connect the end of the remaining old catheter to a new extraperitoneal segment of a new catheter and a piece of a transfer set to connect the adaptors. A novel, yet simple and safe, means of partial peritoneal dialysis catheter replantation when managing catheter injuries is suggested.